Pembinaan Aparatur Pemerintahan dalam Pelaksanaan Tugas di Bagian Umum Sekretariat Kantor Bupati - Matondang, Armansyah (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2015)
This study aims to determine the development of the Government apparatus in performing the tasks in the general section secretariat office of Regent. This study took place in Deli Serdang. Deli Serdang regency is as one of the autonomous regions in Indonesia that are in the administrative area of North Sumatra Province. Empowerment is implementable personnel resources have been carried Division General Secretariat of the Office of the Regent of Deli Serdang through education and training, enforcement of labor discipline, career development and awards. This type of research is descriptive qualitative research. Implementation of the training is kept up preceded by a training needs analysis so that the employees do not vain but right on target.